A Hydrogel-based Electronic Skin for Touch Detection Using Electrical Impedance Tomography - Zhang, Huiyang; Kalra, Anubha; Lowe, Andrew; Yu, Yang; Anand, Gautam (MDPI AG, 2023)
Recent advancement in wearable and robot-assisted healthcare technology gives rise to the demand for smart interfaces that allow more efficient human-machine interaction. In this paper, a hydrogel-based soft sensor for subtle touch detection is proposed. Adopting the working principle of a biomedical imaging technology known as electrical impedance tomography (EIT), the sensor produces images that display the electrical conductivity distribution of its sensitive region to enable touch detection. The sensor was made from a natural gelatin hydrogel whose electrical conductivity is considerably less than that of human skin. The low conductivity of the sensor enabled a touch-detection mechanism based on a novel short-circuiting approach, which resulted in the reconstructed images being predominantly affected by the electrical contact between the sensor and fingertips, rather than the conventionally used piezoresistive response of the sensing material. The experimental results indicated that the proposed sensor was promising for detecting subtle contacts without the necessity of exerting a noticeable force on the sensor.
Keywords: electronic skin; human-machine interface; hydrogel sensor; impedance tomography; soft interface; soft robotics; soft sensor; tomographic imaging; touch sensor; 40 Engineering; 4003 Biomedical Engineering; 46 Information and Computing Sciences; 4009 Electronics, Sensors and Digital Hardware; 4605 Data Management and Data Science; 4016 Materials Engineering; Biomedical Imaging; Bioengineering; 4.1 Discovery and preclinical testing of markers and technologies; 4.2 Evaluation of markers and technologies; 0301 Analytical Chemistry; 0502 Environmental Science and Management; 0602 Ecology; 0805 Distributed Computing; 0906 Electrical and Electronic Engineering; Analytical Chemistry; 3103 Ecology; 4008 Electrical engineering; 4104 Environmental management; 4606 Distributed computing and systems software; Humans; Touch; Electric Impedance; Hydrogels; Tomography, X-Ray Computed; Wearable Electronic Devices; Humans; Hydrogels; Tomography, X-Ray Computed; Touch; Electric Impedance; Wearable Electronic Devices; Humans; Touch; Electric Impedance; Hydrogels; Tomography, X-Ray Computed; Wearable Electronic Devices